2003
DOI: 10.1128/jvi.77.23.12921-12926.2003
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Multiple Human Immunodeficiency Virus Type 1 Variants Is Associated with Faster Disease Progression

Abstract: Human immunodeficiency virus type 1 (HIV-1)-infected individuals develop a genetically diverse virus population over time, but often only a limited number of viral variants are transmitted from a chronic carrier to a newly infected person. Interestingly, many women but few men are infected by multiple HIV-1 variants from a single partner. To determine whether the complexity of the infecting virus population influences clinical outcome, we examined viral diversity in the HIV-1 envelope sequences present at prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
84
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 40 publications
7
84
4
Order By: Relevance
“…The median interval of time for the analyzed sequences was about 35 months (range, 18 to 46 months). In previous studies, we have shown that five (QA284, QA779, QB670, QC168, and QC449) of the nine subjects examined in this study had strictly homogenous envelope sequences early in infection (74,75). Thus, for these subjects, only one early-infection V1-V5 sequence was isolated, and for the remaining four subjects, multiple sequences (median, 3; range, 3 to 4) were isolated from early in infection (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The median interval of time for the analyzed sequences was about 35 months (range, 18 to 46 months). In previous studies, we have shown that five (QA284, QA779, QB670, QC168, and QC449) of the nine subjects examined in this study had strictly homogenous envelope sequences early in infection (74,75). Thus, for these subjects, only one early-infection V1-V5 sequence was isolated, and for the remaining four subjects, multiple sequences (median, 3; range, 3 to 4) were isolated from early in infection (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Infection with multiple T/F viruses is linked to factors that are known to increase overall transmission rates, such as higher risk sex acts and other concurrent sexually transmitted infections [12,[15][16][17][18][19]. Several studies have associated infection with multiple HIV-1 T/F viruses, multiple subtypes, and/or a diverse virus population, with higher pVL setpoint, faster CD4+ T cell decline, earlier need for anti-retroviral therapy and a worse prognosis for the infected individual [14,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals initially infected with a more diverse viral population undergo more rapid HIV-1 disease progression (23,24). However, it is unclear whether these viral characteristics drive poor health outcomes by influencing levels of immune activation.…”
mentioning
confidence: 99%
“…Viral characteristics such as the presence of drug resistance mutations, coreceptor tropism, and the diversity of the proviral population are associated with HIV-1 disease progression (23)(24)(25)(26)(27). For example, individuals initially infected with a more diverse viral population undergo more rapid HIV-1 disease progression (23,24).…”
mentioning
confidence: 99%